Evaluation of dietary crude protein concentrations, fishmeal, and sorghum inclusions in broiler chickens offered wheat-based diet via Box-Behnken response surface design. - Shemil P Macelline (Public Library of Science (PLoS), 2021)
The objective of this study was to investigate the impacts of dietary crude protein (CP), fishmeal and sorghum on nutrient utilisation, digestibility coefficients and disappearance rates of starch and protein, amino acid concentrations in systemic plasma and their relevance to growth performance of broiler chickens using the Box-Behnken response surface design. The design consisted of three factors at three levels including dietary CP (190, 210, 230 g/kg), fishmeal (0, 50, 100 g/kg), and sorghum (0, 150, 300 g/kg). A total of 390 male, off-sex Ross 308 chicks were offered experimental diets from 14 to 35 days post-hatch. Growth performance, nutrient utilisation, starch and protein digestibilities and plasma free amino acids were determined. Dietary CP had a negative linear impact on weight gain where the transition from 230 to 190 g/kg CP increased weight gain by 9.43% (1835 versus 2008 g/bird, P = 0.006). Moreover, dietary CP linearly depressed feed intake (r = -0.486. P < 0.001). Fishmeal inclusions had negative linear impacts on weight gain (r = -0.751, P < 0.001) and feed intake (r = -0.495, P < 0.001). There was an interaction between dietary CP and fishmeal for FCR. However, growth performance was not influenced by dietary inclusions of sorghum. Total plasma amino acid concentrations were negatively related to weight gain (r = -0.519, P < 0.0001). The dietary transition from 0 to 100 g/kg fishmeal increased total amino acid concentrations in systemic plasma by 35% (771 versus 1037 μg/mL, P < 0.001). It may be deduced that optimal weight gain (2157 g/bird), optimal feed intake (3330 g/bird) and minimal FCR (1.544) were found in birds offered 190 g/kg CP diets without fishmeal inclusion, irrespective of sorghum inclusions. Both fishmeal and sorghum inclusions did not alter protein and starch digestion rate in broiler chickens; however, moderate reductions in dietary CP could advantage broiler growth performance.